Genome-wide association study identifies a missense variant at APOA5 for coronary artery disease in Multi-Ethnic Cohorts from Southeast Asia. Issue 1 (December 2017) - Han, Yi; Dorajoo, Rajkumar; Chang, Xuling; Wang, Ling; Khor, Chiea-Chuen; Sim, Xueling; Cheng, Ching-Yu; Shi, Yuan; Tham, Yih; Zhao, Wanting; Chee, Miao; Sabanayagam, Charumathi; et al.
Abstract Recent genome-wide association studies (GWAS) have identified multiple loci associated with coronary artery disease (CAD) among predominantly Europeans. However, their relevance to multi-ethnic populations from Southeast Asia is largely unknown. We performed a meta-analysis of four GWAS comprising three Chinese studies and one Malay study (Total N = 2, 169 CAD cases and 7, 376 controls). Top hits (P  < 5 × 10−8 ) were further evaluated in 291 CAD cases and 1, 848 controls of Asian Indians. Using all datasets, we validated recently identified loci associated with CAD. The involvement of known canonical pathways in CAD was tested by Ingenuity Pathway Analysis. We identified a missense SNP (rs2075291, G > T, G185C) inAPOA5 for CAD that reached robust genome-wide significance (Meta P  = 7.09 × 10−10, OR = 1.636). Conditional probability analysis indicated that the association at rs2075291 was independent of previously reported index SNP rs964184 inAPOA5 . We further replicated 10 loci previously identified among predominantly Europeans (P: 1.33 × 10−7 –0.047). Seven pathways (P : 1.10 × 10−5 –0.019) were identified. We identified a missense SNP, rs2075291, inAPOA5 associated with CAD at a genome-wide significance level and provided new insights into pathways contributing to the susceptibility to CAD in the multi-ethnic populations from Southeast Asia.